Integrating digital technology in language learning for students with disabilities in elementary schools: A critical systematic review - Adams Ogirima Onivehu; Satrio Wahyu Kencono; Amiruddin Hadi Wibowo; Romanda Annas Amrullah (EduStream: Jurnal Pendidikan Dasar, 2025)
This study aims to explore the integration of digital technology in language learning for students with disabilities in inclusive elementary schools. This study used systematic literature review published in the last ten years. The findings shows that iPad applications, digital-based games, and augmented reality are effective in improving reading, writing, and speaking skills for students with various disabilities, including autism, dyslexia, Down syndrome, ADHD, as well as hearing and visual impairments. Tools used include mobile applications, games, and audio-based software. This study emphasized the importance of ongoing teacher training and adequate infrastructure to optimize the use of technology in inclusive education. The results of this study have shown the evidence-based recommendations for more effective and inclusive technology integration practices in elementary schools, filling a gap in the literature regarding the role of technology in language learning for students with disabilities.